To Use or Not Use Intraoperative Neuromonitoring: Utilization of Neuromonitoring During Spine Surgeries and Associated Conflicts of Interest, a Cross-Sectional Survey Study. (March 2022) - Bible, Jesse E.; Goss, Madison
Abstract : Introduction: There are no universal guidelines that dictate the indications for the use of intraoperative neuromonitoring (IONM) in spine surgery resulting in its variable use. The choice to use IONM has been both cited in malpractice lawsuits and insurance claims, but no data exist regarding surgeons' rationale for making this choice. The goal of this study was to assess (1) the use of certain IONM modalities during common spine surgeries, (2) surgeons' rationale for use of IONM, and (3) IONM practices and potential conflicts of interest associated with its use. Methods: Respondents were asked to select each IONM modality they used during 20 different surgical scenarios within the spine followed by rating the importance of several reasons when selecting to use IONM. Finally, the occurrence of conflicts of interest, out-of-network billing, and cost were assessed. Results: Approximately one-half (47%) of respondents who perform anterior cervical diskectomy and fusion/total disk arthroplasty for radiculopathy use IONM, opposed to 76% for myelopathy. The presence of cord compression and/or neurologic symptoms increased IONM use by approximately 30% during trauma cases. Medicolegal was the reason of highest importance when choosing to use IONM (7.4 ± 2.9; mean ± SD), followed by surgeon reassurance (6.2 ± 2.7; P < 0.0001 versus medicolegal) and belief it affects patient outcomes (5.2 ± 3.0; P = 0.004 versus reassurance). Conclusions: Although there is increasing use of IONM, this has not translated to an absolute requirement for every spine surgery. Surgeons are faced with opposing influences of the medicolegal system and insurance payers. Future guidelines on using IONM should not be absolute, but rather should consider the risks of each procedure, along with how patients and surgeons value these risks, in addition to the costs. The findings of this study should help to serve as a guide to surgeons, payers, and courts as contemporary, common practices for the use of IONM during spinal surgical scenarios.